Implementation of cooperative learning model type Jigsaw in social science to increase students’ learning outcome - Dian Permata; Slameto Slameto; Elvira Hoesein Radia (Universitas Pendidikan Ganesha, 2018)
This study aimed at improving learning outcome in social science using cooperative learning model type Jigsaw in social science. The model was implemented in a primary school. This learning model was developed into 2013 curriculum-based learning. We conducted the study into cycle 1 and cycle 2, each consisted of 3 meetings. The research subjects were 4th grade students. The research design was arranged based on planning, action, and reflection. Results show that there is an increase in the number of students passing the minimum requirement. Therefore, Jigsaw can improve students’ learning outcomes.